2009
DOI: 10.1073/pnas.0904850106
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectronic silicon nanowire devices using functional membrane proteins

Abstract: Modern means of communication rely on electric fields and currents to carry the flow of information. In contrast, biological systems follow a different paradigm that uses ion gradients and currents, flows of small molecules, and membrane electric potentials. Living organisms use a sophisticated arsenal of membrane receptors, channels, and pumps to control signal transduction to a degree that is unmatched by manmade devices. Electronic circuits that use such biological components could achieve drastically incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
147
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(151 citation statements)
references
References 30 publications
(31 reference statements)
3
147
0
Order By: Relevance
“…Selective ion transportation through gramicidin A and alamethicin pores reconstituted in lipid bilayers on Si nanowires were designed as a chemical and applied voltage-triggered electronic signal transduction model. 68 Active ion transport was monitored by adopting additional biological components such as a protein ion pump and Na þ /K þ -ATPase on the surface of a CNT transistor. 69 Instead of generating an ionic gradient across the membrane, the molecular binding to the SLB directly affects the electrical behavior of the underlying CNT field-effect transistor (FET) via surface charge modulation.…”
Section: Lipid-nanostructure Hybrids In Sensing Applicationsmentioning
confidence: 99%
“…Selective ion transportation through gramicidin A and alamethicin pores reconstituted in lipid bilayers on Si nanowires were designed as a chemical and applied voltage-triggered electronic signal transduction model. 68 Active ion transport was monitored by adopting additional biological components such as a protein ion pump and Na þ /K þ -ATPase on the surface of a CNT transistor. 69 Instead of generating an ionic gradient across the membrane, the molecular binding to the SLB directly affects the electrical behavior of the underlying CNT field-effect transistor (FET) via surface charge modulation.…”
Section: Lipid-nanostructure Hybrids In Sensing Applicationsmentioning
confidence: 99%
“…To date, lipid bilayers [2] also including ion-channels [3], have been implemented in a field-effect transistor (FET) structure for pH and ionic detection in general. The binding of a protein to a lipid monolayer or bilayer surface has been investigated too [4].…”
Section: Introductionmentioning
confidence: 99%
“…This lipid bilayer performs two functions: it shields the nanowire from the solution species and serves as a native-like environment for membrane proteins that preserves their functionality, integrity, and vectorality. In the past, we showed that this architecture allows us to couple passive ion transport [ 8 ] and active ATP-driven ion transport to the electronic signaling. [ 9 ] In this work, we achieve two goals.…”
Section: Doi: 101002/adma201403988mentioning
confidence: 99%